Improving Students’s Narrative Writing Through Fairy Tales at the Second Year of MTs. DDI Al-Mujahidin Bendoro - Lababa Lababa; Evy Silvyana Adam; Denok Purnamasari; Sam Hermansyah (La Ogi : English Language Journal, 2021)
The objective of the research was fine out whether or not the use of fairy tales improving the students writing narrative text. This research was applied quasi-experimental design. It involved two groups: the experimental group and the control group. The population of this research was the second years students in academic year 2014-2015 of MTs. DDI Al-Mujahidin Bendoro. The total number of population is 48 students, where the researcher take all the population on sample by using census techniqui. The researcher selects VIII.2 as the experimental group and VIII.1 consists of 24 students so the total sample of the research is 48 students. The researcher applied Fairy Tales on the experimental group adn for the control group the student taught using conventional technique. There was one techniques of data collecting applied in this study; they were writing test. The test is use to compare students’ writing achievements. The application of Fairy Tales improve students’ ability Narrative Writing in the Second Year of MTs.DDI Al-mujahidin Bendoro. The achievement in writing narrative text of the students who applied Fairy Tale and those who did no apply Fairy tale had significant difference. It was proved by the mean score in post-test of experimental group was higher than te mean score of control group (79.1667>65.9583) and the t-test value on post-test was higher than t-table(5.058>2.021). base on the data above the researcher conclude the the using Fairy Tales increase students’ writing narrative text.